DIFFERENTIAL DIAGNOSIS OF ROSACEA AND SKIN TUBERCULOSIS AS AN EXAMPLE OF A CLINICAL CASE - M. L. Aripova; S. A. Khardikova (Бюллетень сибирской медицины)
In this paper for a clinical observation of a patient with rosacea, and patients with a flat form of lupus tuberculosis presented a differential clinical diagnosis of tuberculosis of the skin.